COVERAGE OF INTERNATIONAL EVENTS IN THE NEWSPAPER “FERGANA” (Scientific journal of the Fergana State University, 2023)
The article examines the formation of periodicals in Fergana region and the factors that led to this, as well as local newspapers published in the Fergana region during the colonial period.The publication of the Fergana newspaper also analyzes its role in the public life of the country and coverage of social and political processes in foreign countries.